Methodical instructions for the implementation of practical tasks in the discipline "Communications and negotiations" - Chernobrovkina, S. V. (Національний технічний університет "Харківський політехнічний інститут", 2024)
In the context of today's dynamic business environment, the discipline of "Communications and Negotiations" acquires special relevance and significance. Given the high level of competition and rapid changes in market conditions, effective communication and negotiation skills are key to a successful career in marketing. Methodological guidelines are intended to support practical classes in this discipline, aimed at the development of competencies necessary for effective interaction in a professional context. Communication and negotiation are fundamental elements of marketing strategy, from identifying customer needs to designing and implementing effective marketing campaigns. The ability to clearly and convincingly express one's ideas, to understand and take into account the needs and expectations of others, as well as to negotiate effectively are very important for achieving business goals and building lasting relationships with clients. The guidelines cover a wide range of topics, from basic communication and negotiation principles to sophisticated techniques and strategies that can be applied in a variety of marketing scenarios. Special attention is paid to the development of active listening skills, emotional intelligence, persuasive communication, as well as strategic planning and negotiation. These skills are important not only for direct interaction with customers, but also for internal communication in organizations, team and project management. The practical classes provided by these methodological guidelines include various forms of work: from individual tasks to group projects, role-playing games, case studies, analysis of real situations from marketing practice. This approach contributes not only to the assimilation of theoretical knowledge, but also to the development of practical skills, which is extremely important for future professional activity in the field of marketing. The purpose of the guidelines is to provide applicants with the necessary tools and knowledge to develop effective communication and negotiation skills, which are critical to the successful implementation of marketing strategies and the achievement of professional goals.
Keywords: methodical instructions; practical tasks; communications and negotiations; marketing; business environment; market conditions